2015
DOI: 10.1590/0074-02760150215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating anti-Orthopoxvirus antibodies in individuals from Brazilian rural areas prior to the bovine vaccinia era

Abstract: Vaccinia virus naturally circulates in Brazil and is the causative agent of a zoonotic disease known as bovine vaccinia (BV). We retrospectively evaluated two populations from the Amazon and Southeast Regions. BV outbreaks had not been reported in these regions before sample collection. Neutralising antibodies were found in 13 individuals (n = 132) with titres ranging from 100 ≥ 6,400 neutralising units/mL. Univariate analysis identified age and vaccination as statistically significant risk factors in individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…The prevalence of anti-OPV neutralizing antibodies observed in this study (30.1 %) was similar to those reported in a retrospective study performed in 2010 in Amazon region (27.9 %) [ 14 ], and higher when compared to 9.8 % found in another study done with two distinct Brazilian populations [ 16 ]. Although in these two studies [ 14 , 16 ] the populations analyzed had some different characteristics and contexts for OPV serosurvey related to our study, other characteristics are similar, such as subsistence agriculture and farming as the main economic activities. Another Brazilian study carried out in the State of Rio de Janeiro showed a seropositivity of 43 % [ 13 ], where participants were from rural properties affected by outbreaks and most of them were infected, presenting clinical signs and symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of anti-OPV neutralizing antibodies observed in this study (30.1 %) was similar to those reported in a retrospective study performed in 2010 in Amazon region (27.9 %) [ 14 ], and higher when compared to 9.8 % found in another study done with two distinct Brazilian populations [ 16 ]. Although in these two studies [ 14 , 16 ] the populations analyzed had some different characteristics and contexts for OPV serosurvey related to our study, other characteristics are similar, such as subsistence agriculture and farming as the main economic activities. Another Brazilian study carried out in the State of Rio de Janeiro showed a seropositivity of 43 % [ 13 ], where participants were from rural properties affected by outbreaks and most of them were infected, presenting clinical signs and symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Seroprevalence studies of OPV in different populations worldwide have also been used as a marker for the status of protection elicited by vaccination [ 14 , 16 , 23 , 25 , 27 , 28 , 30 , 31 ]. In this study, we have assessed only anti-OPV protective immunity (ie neutralizing antibody titers) and our findings demonstrated that 53.1 % of presumed vaccinated individuals presented OPV neutralizing antibodies, in comparison to 57.1 % of true vaccinees (represented by those with vaccine take), a non-significant difference ( p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, human subclinical infections could not be ruled out. There is evidence of positive serology tests detecting anti‐orthopoxvirus (OPXV) antibodies in habitants of communities that have never had contact with diseased cattle, but have shown protective antibodies to the disease (Figueiredo et al., ; Mota et al., ). Furthermore, OPXV seroprevalence and possible exposure factors related to VACV infections were determined in humans who lived in regions that had outbreaks of BV in Brazil (Costa et al., ).…”
Section: Discussionmentioning
confidence: 99%